291. Digital breast tomosynthesis mean glandular dose evaluation. (December 2018) - Angiocchi, M.C.; Brogna, A.; Di Pasquale, A.; Midili, F.; Mongelli, V.; Siragusa, C.; Micali, A.; Inferrera, P.; Lanzafame, S.; Ielo, I.
Abstract : Purpose: Digital Breast Tomosynthesis (DBT) is a 3D-imaging technique which allows a high-resolution tissues visualization. During a DBT procedure a series of single projection images is acquired over a limited-angle range. The Mean Glandular Dose (MGD) is the dosimetric index currently employed in mammography and it has been adopted as reference dosimetric index in the European guidelines[1] . Aim of this work was to evaluate the MGD in DBT procedures in order to study the unavoidable cumulative dose (DBT + conventional mammography) increasing of the whole diagnostic exam. Methods: 50 2D breast examinations with associate DBT investigations of doubt sign were selected. MGD consolle values and all the exposure information (kV, mAs, HVL, tube/filter combination, breast thickness) were recorded for each 2D view and DBT acquisition. Air Kerma was measured by the use of a Piranha Detector and it was evaluated as a mAs function for fixed KVs and tube/filter combinations. These measurements allowed to calculate the MGD, using tabulated g-, c-, s- and T-Monte Carlo factors obtained by radiation transport calculations, according to European guidelines. g-, c-, s-factors convert incident air kerma to absorbed dose for a specific composition and size breast; T-factor[2] correct the MGD for the angle projection. Results: For single breast DBT procedures average MGD value was 1.66 ± 0.51 mGy with 2.90 mGy max value. Average dose for single breast due to all conventional projection was 3.67 ± 1.03 mGy. The average cumulative dose for single breast was 4.77 ± 1.80 mGy. Therefore, an average increase of 34.7% of the cumulative dose was registered when a DBT investigation was performed. Conclusion: DBT procedures involve an important benefit for the purpose of a more exhaustive diagnostic information with a limited increasing risks associated with the absorbed dose.